Effects of 6-weeks Bhastrika Pranayama Intervention on health-related components of physical fitness - Baljinder S. Bal; Parmjit Kaur; Davinder Singh; Manoj Bhardwaj (Physical Education of Students)
Background and Study Aim. The present study investigated the effects of 6-weeks bhastrika pranayama intervention (BPI) program on health-related components of physical fitness.